Asymmetric post-translational modifications regulate the nuclear translocation of STAT3 homodimers in response to leukemia inhibitory factor - Diallo, Mickael (2024)
Funding Information: We acknowledge the BioISI/FCUL Microscopy Facility, a node of the Portuguese Platform of BioImaging supported by FEDER funds (Ref. PPBI-POCI-01-0145-FEDER-022122). The mass spectrometry-based proteomics approach was performed at the i3S Proteomics Scientific Platform with the assistance of Hugo Osório, and had support from the Portuguese Mass Spectrometry Network, integrated in the National Roadmap of Research Infrastructures of Strategic Relevance (ROTEIRO/0028/2013; LISBOA-01-0145-FEDER-022125). FH was supported by Project LISBOA-01-0145-FEDER-007660 (Cellular Structural and Molecular Microbiology) funded by FEDER funds through COMPETE2020 – Programa Operacional Competitividade e Internacionalização (POCI). FH, FRP and MSR were supported by Centre grants from Fundação para a Ciência e Tecnologia to the BioISI Research Unit (Refs. UIDB/04046/2020 and UIDP/04046/2020, https://doi.org/10.54499/UIDB/04046/2020 ) and by individual grants through Fundação para a Ciência e Tecnologia (PTDC/MED-NEU/31417/2017 to FH and PTDC/FIS-MAC/2741/2021 to MSR, https://doi.org/10.54499/PTDC/FIS-MAC/2741/2021 ). MD was supported by a research contract under FCT grant Ref. PTDC/MED-NEU/31417/2017. RV, FM and AAC were supported by PhD fellowships from Fundação para a Ciência e Tecnologia (Refs. PD/BD/128163/2016, SFRH/BD/133220/2017 and UI/BD/153051/2022, respectively). Funded by the European Union (TWIN2PIPSA, GA 101079147). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or European Research Executive Agency (REA). Neither the European Union nor the granting authority can be held responsible for them. Funding Information: We acknowledge the BioISI/FCUL Microscopy Facility, a node of the Portuguese Platform of BioImaging supported by FEDER funds (Ref. PPBI-POCI-01-0145-FEDER-022122). Mass spectrometry was carried out with support from the Portuguese Mass Spectrometry Network, integrated in the National Roadmap of Research Infrastructures of Strategic Relevance (ROTEIRO/0028/2013; LISBOA-01-0145-FEDER-022125). FH was supported by Project LISBOA-01-0145-FEDER-007660 (Cellular Structural and Molecular Microbiology) funded by FEDER funds through COMPETE2020 – Programa Operacional Competitividade e Internacionalização (POCI). FH, FRP and MSR were supported by Centre grants from Fundação para a Ciência e Tecnologia to the BioISI Research Unit (Refs. UIDB/04046/2020 and UIDP/04046/2020, https://doi.org/10.54499/UIDB/04046/2020 ) and by individual grants through Fundação para a Ciência e Tecnologia (PTDC/MED-NEU/31417/2017 to FH and PTDC/FIS-MAC/2741/2021 to MSR, https://doi.org/10.54499/PTDC/FIS-MAC/2741/2021 ). MD was supported by a research contract under FCT grant Ref. PTDC/MED-NEU/31417/2017. RV, FM and AAC were supported by PhD fellowships from Fundação para a Ciência e Tecnologia (Refs. PD/BD/128163/2016, SFRH/BD/133220/2017 and UI/BD/153051/2022, respectively). Funded by the European Union (TWIN2PIPSA, GA 101079147). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or European Research Executive Agency (REA). Neither the European Union nor the granting authority can be held responsible for them. Publisher Copyright: © The Author(s) 2023.